The Influence Of Teacher Training And Teacher Competency On Teacher Performance At Sehati Vocational School - Erika Noviana Fairus; Suroso; Flora Patricia Anggela (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This study aims to analyze the influence of teacher training and teacher competency on the performance of educators at SMK Sehati Karawang. Research method—The research involved a population of 50 teachers, employing a saturated sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. Result— The findings revealed that teacher training does not significantly affect teacher performance. In contrast, teacher competency has a positive and significant impact, as indicated by a t-count of 6.230, which exceeds the critical t-table value of 2.002. Simultaneously, the overall model demonstrated a significant influence on teacher performance, with an F-value of 150.305, surpassing the critical value of 3.20. Conclusion— The study concludes that while teacher training may not enhance performance, teacher competency is critical for improving educator effectiveness. These insights suggest a need for focused initiatives to develop teacher competency in educational environments.